Social engineering approach to air quality challenge: The case of Kathmandu - Arya, Ramesh C (Occasional Papers in Sociology and Anthropology, 2008)
The PDF of this file is 1,516 kbytes in size and therefore will take a long time to download if you click on the PDF link below. If you would like the file to be sent to you by email, please send a request to info@nepjol.info. Please include the citation below in your request. DOI: 10.3126/opsa.v6i0.1105 Occasional Papers in Sociology and Anthropology Vol.6 2000 p.112-122